Effectiveness of bereavement counselling through a community‐based organization: A naturalistic, controlled trial. (29th August 2017) - Newsom, Catherine; Schut, Henk; Stroebe, Margaret S.; Wilson, Stewart; Birrell, John; Moerbeek, Mirjam; Eisma, Maarten C.
Abstract : This controlled, longitudinal investigation tested the effectiveness of a bereavement counselling model for adults on reducing complicated grief (CG) symptoms. Participants ( N  = 344; 79% female; mean age: 49.3 years) were adult residents of Scotland who were bereaved of a close relation or partner, experiencing elevated levels of CG, and/or risks of developing CG. It was hypothesized that participants who received intervention would experience a greater decline in CG levels immediately following the intervention compared to the control participants, but the difference would diminish at follow‐up (due to relapse). Data were collected via postal questionnaire at 3 time points: baseline (T), post‐intervention (T + 12 months), and follow‐up (T + 18 months). CG, post‐traumatic stress, and general psychological distress were assessed at all time points. Multilevel analyses controlling for relevant covariates were conducted to examine group differences in symptom levels over time. A stepwise, serial gatekeeping procedure was used to correct for multiple hypothesis testing. A main finding was that, contrary to expectations, counselling intervention and control group participants experienced a similar reduction in CG symptoms at postmeasure. However, intervention participants demonstrated a greater reduction in symptom levels at follow‐up ( M =  53.64; d =  .33) compared to the control group ( M =  62.00). Results suggest community‐based bereavement counselling may have long‐term beneficial effects. Further longitudinal treatment effect investigations with extensive study intervals are needed.